PENETAPAN HARGA OPSI SAHAM DENGAN MENGGUNAKAN MODEL BLACK-SCHOLES - YOSMAR, SISKA (Sainstek : Jurnal Sains dan Teknologi, 2012)
The problem of the research was about the loss suffered by some investors due to the price changes in the future. In order to maximize the profit or minimize the loss, the investors should estimate the option price; both call option and put option. This research tried to describe the stock phenomena and to establish the Black-Scholes model for option pricing.Key words: call option, put option, Black-Scholes model